Exploration of esg growth as a driver behind mergers and acquisitions - Pflegpeter, Lisa (2022)
This thesis investigates the association between ESG scores and M&A activity. This is done by evaluating whether low-ESG acquirors target high-ESG firms to enhance their ESG ratings. A sample of 151 M&A deals between 2010 and 2018 is used for which ESG data for targets and acquirors, as well as post-acquisition scores, are available. Through utilizing quantitative analyses and ESG scores as key measures, the study concludes that the acquirors’ ESG scores do not increase within one year post-deal-announcement but suggests that acquirors target firms with higher ESG scores than their own.